Priority Analysis Of Big Data-Based Public Service Maladministration Supervision - Andi Setyo Pambudi; Istiqlal Abadiyah Sukma Putri; Devy Paramitha Agnelia; Muhammad Reffo Bhawono Yudho (Jurnal Administrasi Publik, 2025)
Public service supervision in Indonesia is supported by two crucial regulations: Law Number 25 of 2009 and Law Number 37 of 2008. The determination of public service supervision priorities must be quick because of the high public demand for transparency and accountability, along with increasing access to information and public participation in supervision. Although the quality of public service providers has improved, the resolution of public complaints remains unprioritized due to budget constraints. Therefore, establishing clear oversight priorities is essential to enable the Ombudsman to operate more optimally, effectively, and efficiently within the limits of its available capacity and resources. This study aims to analyze the top issues of public complaint substance related to public services through 2 (two) approaches: manual analysis based on data from the Indonesian Ombudsman and big data with Intelligence Media Analytics (IMA). The method used is descriptive-explorative analysis based on literature studies by comparing complaint data from the Indonesian Ombudsman Annual Report and the results of the IMA analysis. The study results show that agrarian, personnel, education, and police are the 4 (four) main substances most often reported in both approaches. The alignment of these findings reinforces the urgency of using a big data-based approach so that its use becomes essential in determining real-time and evidence-based supervision priorities to increase the effectiveness of supervision of public service maladministration in the future.